2017
DOI: 10.1536/ihj.16-468
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Grafting with Arterial Conduits in the Elderly

Abstract: SummaryAlthough improved long-term outcomes obtained with the use of arterial grafts for coronary revascularization in comparison with the traditional association of a single arterial and saphenous vein grafts have been demonstrated in the overall population, the efficacy of this newer technique in the elderly is difficult to prove because their shorter life expectancy due to advanced heart disease, associated with severe comorbidities. Moreover, more widespread use of this technique is limited by the concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Pulmonary infection is the most common complication in CABG, which has a rapid onset and dangerous condition. It has a great impact on the prognosis of patients [6][7][8][9]. It brings huge obstacles to the work and spirit of patients, as well as huge economic burden and labor loss to families and society [10].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary infection is the most common complication in CABG, which has a rapid onset and dangerous condition. It has a great impact on the prognosis of patients [6][7][8][9]. It brings huge obstacles to the work and spirit of patients, as well as huge economic burden and labor loss to families and society [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous reports supported the use of the RA conduit in preference to the saphenous vein (SV) graft, [3][4][5][6][7][8][9][10] while other studies suggested the opposite. [11][12][13][14] Ongoing doubt and debate remained regarding the efficacy of the RA as an aorta-coronary conduit, with few solid data regarding long-term patency. Also, consensus has yet to emerge among experts as to whether the RA conduit was superior long-term patency to the SV graft.…”
mentioning
confidence: 99%
“…1) For decades, in situ LIMA grafting to the left anterior descending artery (LAD) is considered as the "gold standard" of coronary revascularization. 2,3) To maximize the benefits of the LIMA conduit, previous studies reported a sequential anastomotic technique that uses LIMA for grafting more than one major epicardial coronary artery at one time. [4][5][6][7] The skeletonized harvesting method of internal mammary artery achieves maximal length and facilitates the ease of sequential grafting.…”
mentioning
confidence: 99%